Kontrola i nadzór nad działalnością finansową jednostek samorządu terytorialnego - Laskowski, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The idea of the 1998 reform of public administration in Poland was the organizational and financial separation of local and state authorities. Simultaneously new control and supervision mechanisms were introduced in order to detect and correct irregularities in the financial sector of self government units. The main element of the newly created system are regional account chambers. They fulfill three main functions: they control, supervise and give opinion. The regional account chamber is obliged to provide complex financial control of self government units' financial activities at least once in four years' period or at the request of interested unit.The financial control in the sector of public finances concerns the processes related to accumulation and distribution of public resources as well as property management. In the matters that concern financial control, Polish regulations are convergent with the EU ones. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 534-540